Studies Of Amino Acid Component And Microflora In Climbing Perch Wadi - Khairina, Rita; Khotimah, Iin Khusnul (Jurnal Teknologi Pertanian, 2006)
The research of microflora and amino acids component in climbing perch wadi had been done.Â  Aims of this research are to know amino acids composition in fresh fish and climbing perch wadi; and to know kind of halofilic bacterial (until genus level) that have a role during climbing perch wadi fermentation process.Â  Wadi is tradisional fermentationÂ  product of fish that have fishÂ  fermentation specific aroma with salty taste.Â  Was the processes by dry pickling in closed chamber with hight concentration salt (â¥ 25% w/w). The result, arranged component of amino acids in fresh climbing perch is the sameÂ  of climbing perch wadi, but the compositions are decreased during fermentation process. Isolation, characterization and identification of bacterial were done, obtain three kinds ofÂ  bacterial fromÂ  Acinetobacter, Enterobacteriaceae, and Brucella genus, and the dominant genus group is Acinetobacter. Â  Key words: microflora, amino acid component, wadi, climbing perch